If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + -11 = 16 Reorder the terms: -11 + 8m = 16 Solving -11 + 8m = 16 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 8m = 16 + 11 Combine like terms: -11 + 11 = 0 0 + 8m = 16 + 11 8m = 16 + 11 Combine like terms: 16 + 11 = 27 8m = 27 Divide each side by '8'. m = 3.375 Simplifying m = 3.375
| x/3+2=x/5+4 | | 4v^2-13v+10=0 | | 2(2n+2)=6(8n+3)+3 | | 48=5/8f+23 | | -4k=42.4 | | 0.7x-4.1=0.1 | | 9(x-3)/6=3(x+8)/13 | | -x/5+5=15 | | 2y^3+5y^2-3y=0 | | 1x+.15x=52.19 | | m^2-16m=8 | | 1.5=4x-8.5 | | z-7=8 | | 4x+2=4(x-2) | | 2x-2+8x=5 | | lnx^2=0 | | 11.4+10.2*10.9-7.3= | | x//5-=x/5 | | z-12=-9 | | -5(5x-1)+5=-25x+10 | | 4y+10=30 | | log(4a-112)=3 | | x^5-4x^3-x^2+5x+2=0 | | 2x-15x-53=0 | | 8x+x^2=11 | | u(u)+5u+4=0 | | a^2-13a+10=0 | | 20-16t^2+32t=0 | | 3[6x-2(y-3)]= | | (3X+5)+(2X-1)=(X-2)-(3X-4) | | x^3-6x^2+9x+2=x^2-7x+14 | | 2(7x+1)=14x+2 |